Protein Diversity and Immune Specificity of Hemocyanin From Shrimp Litopenaeus vannamei - Zhao, Xianliang; Qiao, Jie; Zhang, Pei; Zhang, Zehui; Aweya, Jude Juventus; Chen, Xiaohan; Zhao, Yongzhen; Zhang, Yueling (Frontiers in Immunology, 2021)
Hemocyanin is an important non-specific innate immune defense molecule with phenoloxidase, antiviral, antibacterial, hemolytic, and antitumor activities. For better understanding the mechanism of functional diversity, proteomics approach was applied to characterize HMC expression profiles from Litopenaeus vannamei. At first, hemocyanin was purified by Sephadex G-100 and DEAE-cellulose (DE-52) columns from shrimp serum, and thirty-four protein spots were identified as HMC on the 2-DE gels. Furthermore, we found that nine HMC spots about 75 kDa or 77 kDa were regulated by Streptococcus agalactiae and Vibrio parahaemolyticus infection at 6, 12 and 24 h. In addition, six different pathogen-binding HMC fractions, viz. HMC-Mix, HMC-Vp, HMC-Va, HMC-Vf, HMC-Ec and HMC-Sa, showed different agglutinative and antibacterial activities. Moreover, lectin-blotting analysis showed significant differences in glycosylation level among HMC isomers and bacteria-binding HMC fractions. Particularly, the agglutinative activities of the HMC fractions were almost completely abolished when HMC was deglycosylated by O-glycosidase, which suggest that O-linked sugar chains of HMC played important roles in the innate immune recognition. Our findings demonstrated for the first time that L. vannamei HMC had molecular diversity in protein level, which is closely associated with its ability to recognize diverse pathogens, whereas glycan modification probably contributed to HMC’s diversity and multiple immune activities.